The role of group play therapy in improving adolescents’ social interaction - Nazri, Eiryeen Nathasya; Ahmad, Noorlila; Ahmad, Norkhaimah Khaiessa; Abu Bakar, Abu Yazid (Scientific Research Publishing, 2022)
The global pandemic Covid-19 is affecting individuals’ health, physically and financially. During the outbreak, a state of lockdown significantly impacted adolescents’ social interaction. Being alone is a common phenomenon. However, avoiding social interaction due to low self-esteem or insecurities eventually will lead to psychological problems in the long run. Hence, this research has a two-fold view. First, to improve communication skills using group play therapy, and to enhance adolescents’ acceptance in building new relationships with others and their age group. This research employed an action research process from the cycle process planning until the reflecting stage from two volunteer adolescents and referred by the class teachers. This study examines group play therapy through five-session activities to trigger social interaction during ice breaking, expressing feelings, sharing a common interest, friendship chains, and values others. Throughout the sessions, it was found that adolescents developed their social interaction with new people involving communication skills. In fact, self-acceptance was constructed based on analyzing the participants’ and friends’ revelations in the interviews. Thus, it can be implied from the research findings that group play therapy improved positive social interaction and was used to avoid social awkwardness.